2015
DOI: 10.1186/s12889-015-2520-9
|View full text |Cite
|
Sign up to set email alerts
|

Small-area spatio-temporal analyses of participation rates in the mammography screening program in the city of Dortmund (NW Germany)

Abstract: BackgroundThe population-based mammography screening program (MSP) was implemented by the end of 2005 in Germany, and all women between 50 and 69 years are actively invited to a free biennial screening examination. However, despite the expected benefits, the overall participation rates range only between 50 and 55 %. There is also increasing evidence that belonging to a vulnerable population, such as ethnic minorities or low income groups, is associated with a decreased likelihood of participating in screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Our results show that geographical clusters of mammography adherence can be identified in an urban setting like Geneva, Switzerland. While similar clusters have been previously reported in other circumstances using ecological data [18-19,7,20], we report it for the first time using data at the individual level by considering geographic space as a continuum rather than according to predefined administrative units.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results show that geographical clusters of mammography adherence can be identified in an urban setting like Geneva, Switzerland. While similar clusters have been previously reported in other circumstances using ecological data [18-19,7,20], we report it for the first time using data at the individual level by considering geographic space as a continuum rather than according to predefined administrative units.…”
Section: Discussionsupporting
confidence: 79%
“…Previous ecological studies, such as Lemke et al, have suggested that clustering was due to low-income and immigrant populations inhabiting neighbourhoods with low mammography adherence [19]. Ecological studies are prone to the ecological fallacy with conclusions about individuals being drawn from group-level analyses; they are based on the mean behaviour of each group and are thereby unable to assess within-group variation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that geographical clusters of mammography adherence can be identified in an urban setting like Geneva, Switzerland. While similar clusters have been previously reported in other circumstances using ecological data, we report it for the first time using data at the individual level by considering geographic space as a continuum rather than according to predefined administrative units.…”
Section: Discussionsupporting
confidence: 64%
“…Previous ecological studies, such as Lemke et al, have suggested that clustering was due to low‐income and immigrant populations inhabiting neighborhoods with low mammography adherence . Ecological studies are prone to the ecological fallacy with conclusions about individuals being drawn from group‐level analyses; they are based on the mean behavior of each group and are thereby unable to assess within‐group variation.…”
Section: Discussionmentioning
confidence: 99%
“…1 (with further details in Appendix C). In total, 13 unique primary studies (representing 14 articles) from seven countries were included in the review: England (n = 4, from 5 articles) [ [23] , [24] , [25] , [26] , [27] ], France (n = 3) [ 19 , 28 , 29 ], Germany (n = 1) [ 30 ], Italy (n = 1) [ 31 ], Sweden (n = 1) [ 18 ], the Netherlands (n = 1) [ 17 ] and Turkey (n = 2) [ 32 , 33 ]. All countries ran screening programmes, although it is acknowledged that, in Turkey, breast cancer screening is still performed primarily on an opportunistic basis [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%